2012
DOI: 10.1111/j.1365-3040.2012.02580.x
|View full text |Cite
|
Sign up to set email alerts
|

High relative air humidity and continuous light reduce stomata functionality by affecting the ABA regulation in rose leaves

Abstract: Plants developed under high (90%) relative air humidity (RH) have previously been shown to have large, malfunctioning stomata, which results in high water loss during desiccation and reduced dark induced closure. Stomatal movement is to a large extent regulated by abscisic acid (ABA). It has therefore been proposed that low ABA levels contribute to the development of malfunctioning stomata. In this study, we investigated the regulation of ABA content in rose leaves, through hormone analysis and b-glucosidase q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
108
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(135 citation statements)
references
References 45 publications
16
108
2
Order By: Relevance
“…Interestingly, while we show here that foliar ABA appears to drive stomatal responses to changes in VPD in angiosperms, a number of studies have shown that the exposure of angiosperm leaves to low humidity is a critical prerequisite for delivering normal stomatal responses to ABA and that high humidity can desensitize stomata to ABA (Arve et al, 2013;Pantin et al, 2013b;Aliniaeifard et al, 2014). This interaction is more likely due to low humidity being a strong upregulator of both ABA synthetic and signaling genes (Pantin et al, 2013b) than being due to changes in stomatal or leaf anatomy at high humidity (Aliniaeifard et al, 2014).…”
Section: Foliar Aba Regulates the Stomatal Response To Vpd In Angiospcontrasting
confidence: 49%
“…Interestingly, while we show here that foliar ABA appears to drive stomatal responses to changes in VPD in angiosperms, a number of studies have shown that the exposure of angiosperm leaves to low humidity is a critical prerequisite for delivering normal stomatal responses to ABA and that high humidity can desensitize stomata to ABA (Arve et al, 2013;Pantin et al, 2013b;Aliniaeifard et al, 2014). This interaction is more likely due to low humidity being a strong upregulator of both ABA synthetic and signaling genes (Pantin et al, 2013b) than being due to changes in stomatal or leaf anatomy at high humidity (Aliniaeifard et al, 2014).…”
Section: Foliar Aba Regulates the Stomatal Response To Vpd In Angiospcontrasting
confidence: 49%
“…The reasons for altered stomatal morphology are not yet understood. Recent studies have suggested that stomatal malfunctioning in low RH-grown leaves is a consequence of a high foliar abscisic acid content during leaf development at decreased atmospheric humidity, compared with leaves grown in a more humid atmosphere [21,74]. However, it has been shown that shorter stomata have faster response times than larger ones [24].…”
Section: Gas Exchange Measurementsmentioning
confidence: 97%
“…Conversely, high RH induces ABA catabolism and stomatal opening [24]. Interestingly, plants grown under high RH show a weak stomatal response to ABA [25,26]. We therefore hypothesized that high RH around young leaves could be the primary environmental signal maintaining stomatal insensitivity to ABA, whereas older leaves are sensitized to ABA by being exposed to lower ambient RH.…”
Section: Stomatal Sensitivity To Aba Increases During Leaf Developmentmentioning
confidence: 97%